2009
DOI: 10.1021/jp906716g
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties and Singlet Oxygen Production by Ruthenium(II) Complexes of Benzo[i]dipyrido[3,2-a:2′,3′-c]phenazine: Spectroscopic and TD-DFT Study

Abstract: The photophysical properties of a series of Ru(II) complexes containing benzo[i]dipyrido[3,2-a:2',3'-c]phenazine (dppn) as a ligand are reported. Transient absorption spectroscopy studies indicate that, in contrast to related Ru(dppz) complexes (dppz = dipyrido[3,2-a:2',3'-c]phenazine), the excited state of all the dppn systems is a long-lived pipi* triplet state. Computational studies (DFT and TD-DFT) confirm that the excited state is based on the dppn ligand. Near-infrared luminescence studies reveal that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
93
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 57 publications
11
93
0
1
Order By: Relevance
“…Polypyridyl complexes 1 a-4 a [31][32][33] and the cyclometalated complex 4 b [34] have been synthesized previously. Complexes 1 b-3 b were synthesized by reacting [Ru(ppy)(bpy)-(NCCH 3 ) 2 ]PF 6 [35] with an equimolar amount of the requisite aromatic ligand in refluxing ethanol.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Polypyridyl complexes 1 a-4 a [31][32][33] and the cyclometalated complex 4 b [34] have been synthesized previously. Complexes 1 b-3 b were synthesized by reacting [Ru(ppy)(bpy)-(NCCH 3 ) 2 ]PF 6 [35] with an equimolar amount of the requisite aromatic ligand in refluxing ethanol.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The presence of long‐lived 3 IL excited states (μs timescale) has been evidenced by time‐resolved spectroscopy coupled with electrochemistry and DFT calculations 29. 30 The relative position of 3 IL with respect to the low‐lying 3 MLCT states may control the photophysics of this class of complexes 29. 30…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DNA photocleavage experiments were carried out by gel-electrophoresis separation of pBR322 DNA after incubation with 1 -6 and irradiation at 365 nm under aerobic conditions. Near-IR luminescence experiments revealed that the complex is an efficient 1 O 2 sensitizer with yields as high as 83% [54]. However, complex 5 showed potent activity (Fig.…”
mentioning
confidence: 99%